BRS Notável: a medium-early-maturing, disease-resistant Carioca common bean cultivar with high yield potential - Pereira,Helton Santos (2012)
BRS Notável is a common bean cultivar with carioca grain, suitable for cultivation in 20 Brazilian states. It is a medium-early-maturing cultivar, with an average yield of 2,261 kg ha-1, 8.5% higher than the controls, a high yield potential (4,472 kg ha-1), lodging tolerance and resistance to anthracnose, fusarium wilt, common bacterial blight, and curtobacterium wilt.